2010
DOI: 10.1007/s11033-010-0206-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification and analysis of the promoter region of the human DHCR24 gene: involvement of DNA methylation and histone acetylation

Abstract: Mutations in the DHCR24 gene, which encodes the cholesterol biosynthesis enzyme 3ß-hydroxysterol-∆24 reductase, result in an autosomal recessive disease called desmosterolosis. Further, reduced expression of DHCR24 is found in the temporal cortex of Alzheimer's disease patients. This suggests that variability in the regulatory regions of DHCR24 may contribute to the development of this neurodegenerative disease. In this work, we functionally characterised the proximal fragment of the human DHCR24 gene, for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 57 publications
3
15
0
Order By: Relevance
“…They did not report if cholesterol levels were altered by the treatment. Drzewinska et al (2011) reported that 24-dehydrocholseterol reductase ( DHCR24 ), which is not reported in the abovementioned studies, was induced by treatment with either TSA or 5-azacytidine (5AZA) in some, but not all, of the cell types tested. Taken together, the data available in connection with these studies indicates that epigenetic mechanisms are important for the regulation of the cholesterol synthesis pathway.…”
Section: Cholesterol Synthesismentioning
confidence: 87%
“…They did not report if cholesterol levels were altered by the treatment. Drzewinska et al (2011) reported that 24-dehydrocholseterol reductase ( DHCR24 ), which is not reported in the abovementioned studies, was induced by treatment with either TSA or 5-azacytidine (5AZA) in some, but not all, of the cell types tested. Taken together, the data available in connection with these studies indicates that epigenetic mechanisms are important for the regulation of the cholesterol synthesis pathway.…”
Section: Cholesterol Synthesismentioning
confidence: 87%
“…Drzewinska et al [30] showed that methylation of the DHCR24 promoter region affects transcriptional efficiency. DNA methylation mediates transcriptional repression via binding of the methylated DNA-binding protein or preserves the binding of transcription factors to their motifs.…”
Section: Discussionmentioning
confidence: 99%
“…In fear-conditioned AD mouse models, the HDAC inhibitors such as trichostatin A (TSA), VPA, SAHA (vorinostat) or sodium butyrate increase the synapse remodeling and enhance the contextual memory by regulating H3/H4 acetylation of relevant gene promoters to enhance hippocampal long-term potentiation (Fischer et al, 2007, 2010; Francis et al, 2009; Guan et al, 2009; Kilgore et al, 2010; Ricobaraza et al, 2012). At the molecular level, sodium butyrate recruits acetylated H3/H4 to the DHCR24 enhancer and increases gene expression which is reduced in the temporal cortex of an AD patient’s brain (Drzewinska et al, 2011). …”
Section: Histone and Non-histone Acetylation And Alzheimer’s Diseasementioning
confidence: 99%